Implementation Of Education And Training For Teachers In Improving The Quality Of Education - Mujahid, Tamimi (Yana Research, 2025)
The availability of reliable human resources, apart from capital and facilities, determines the success of an agency or organization. Principals, teachers, and staff are important members of the human resources management team and are excellent resources in providing educational services to students. This research uses a qualitative research method where data collection uses the interview method and the resource person in this research is the school principal, the place of this research is SMP SWT Utama Medan. In terms of school quality improvement programs, school principals have programs to determine activities that are tailored to the goals of developing institutions. This can be seen from the teacher always providing innovation related to quality, lots of ideas, suggestions and creativity.